Statues and Vandalism in Armenia and North Macedonia: Expressions of Official and Unofficial Nationalist Identity - Kassab, Hanna Samir (Տիգրան Մեծ)
In Skopje, there are many statues of heroes and patriots controversially claimed by Greece and Bulgaria. One statue now labeled ‗warrior on the horse‘ due to Greek pressure was designed to be Alexander the Great. People still refer to the statue as Alexander, a testament to the persistence of nationalist beliefs. In Yerevan, the Mother Armenia statue looks upon Mount Ararat in modern day Turkey. She wields a sword, as if to say ―it‘s not over‖. The same might be said about the graffiti in both states as both are heavily nationalistic in nature. These acts of graffiti/vandalism communicate a message of disorder and dissatisfaction against the state. These official and unofficial nationalist sentiments are expressed because of the need to recover, in North Macedonia‘s case, a long suppressed sense of national identity, and in the Armenian sense, a nationalism under attack. Nationalism in this sense is an expression of cultural revitalization, an essentially Postcolonial need to recover notions of self. This theoretical underpinning will serve as a baseline from which to apply the ethnographic findings of my trips to these locations.
Keywords: Postcolonialism; Culture